EFFECT OF GROUND AND NON-GROUND BAY LEAF (Syzygium polyanthum) ON AORTIC THICKNESS IN WISTAR RATS - Suci Rizki Nurul Aeni; Fitri Nurmahamidah; Hafizah Ilmi Sufa; Syaeful Bahri (Meditory : The Journal of Medical Laboratory, 2026)
Background: Hypercholesterolemia promotes aortic wall thickening and increases cardiovascular risk. Although Syzygium polyanthum (bay leaves) has antioxidant and hypocholesterolemic properties, evidence comparing crushed and non-crushed decoctions remains limited. Objective: This study aimed to compare the effects of crushed and non-crushed bay leaf decoctions on aortic wall thickness in hypercholesterolemic Wistar rats (Rattus norvegicus). Methods: A randomized post-test only control group study was conducted using 40 male Wistar rats assigned to eight groups. Bay leaf decoctions (crushed or non-crushed; 0.52%, 0.72%, and 0.92%) were administered orally for 14 days. Aortic wall thickness was assessed histologically and analyzed using the Kruskal–Wallis and Dunn's tests. Results: A significant difference in aortic wall thickness was observed among the groups (p = 0.040). The lowest mean aortic wall thickness was observed in the 0.92% crushed bay leaf decoction group (92.00 ± 29.20 μm), which was lower than that of the hypercholesterolemic control group (188.00 ± 29.24 μm). Conclusions: Crushed bay leaf decoction, especially at 0.92%, more effectively reduced aortic wall thickness than the non-crushed preparation. Further studies are needed to confirm the underlying mechanisms.